A Venture with Stanger: An Exploratory Research to the Using of Online Co-founder Matchup Platforms in Entrepreneurial Team Formation - Ma, Chih-Chung (2015)
This exploratory research looks into the new emerging method of entrepreneurial team formation by using the online co-founder matching platforms that not yet receive much attention from the scholars. By applying the current theoretical to the recognised four-step process of the internet-intermediated venture team formation from the interview with entrepreneurs who have the experience of using the platforms, this research discovers the support to the existence of the resource-seeking approach and the interpersonal attraction approach in the process of internet-intermediated venture team formation. The resource-seeking intentions is argued to be the motivation of the initiation of the using of the online platforms, while the interpersonal attraction approach could affect the co-founder selection and also function as a mean for entrepreneurs to secure the resources. Furthermore, the internet-intermediated venture team formation not only could be the solution for the entrepreneurs who cannot find the co-founders through offline social network, but more importantly, might challenge the current theoretical frameworks of the entrepreneurial team formation that assume the social network is the only source of the cofounder.